2021
DOI: 10.3390/agronomy11010098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vermicompost, Compost and Digestate as Commercial Alternative Peat-Based Substrates on Qualitative Parameters of Salvia officinalis

Abstract: Peat is a common substrate used for the cultivation of potted plants. However, the use of peat in horticulture has recently been questioned from an environmental standpoint, since it is a non-renewable resource and plays a major role in atmospheric CO2 sequestration. The aim of this work was to assess the potentialities of substrates obtained from vermicompost, compost and anaerobic digestion processes to partially substitute peat for sage (Salvia officinalis L.) cultivation. Therefore, we planned an experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…The different fertilizer sources and HA applications increased the EOC and EO components of Ocimum basilicum var. purple 53 , Arachis hypogaea L. 54 , and Salvia officinalis 13 , which agree with the present research (Fig. 4 b and Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The different fertilizer sources and HA applications increased the EOC and EO components of Ocimum basilicum var. purple 53 , Arachis hypogaea L. 54 , and Salvia officinalis 13 , which agree with the present research (Fig. 4 b and Table 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies are revealing that the application of organic fertilizers and bio-stimulants improve plant height, fresh and dry matter yield, micronutrients uptake, the number of branches, and essential oil content (EOC) in medicinal plants such as Mentha piperita L. 12 , Salvia officinalis 13 , Mentha arvensis L. 14 , and Carum carvi L. 15 . Hassan and Fahmy reported that the foliar application of HA significantly increased the yield components and EOC in chamomile 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Organic agriculture and horticulture are especially important targets for vermicompost application, in a view of providing balanced nutrition for crop needs and soil sustainability through enhanced microbiological activity [16,17]. Another especially promising direction in horticulture is the inclusion of vermicompost as a major component in substrate mixes for the design of alternative plant-growing media to replace peat-based mixes [18,19]. While previous studies in this direction have produced promising results, physicochemical interactions between vermicompost and other substrate components, and their possible effect on the beneficial activity of vermicompost, have not been experimentally assessed.…”
Section: Introductionmentioning
confidence: 99%
“…At a dose of 4 kg m −2 , a mixture of two types of spent mushroom waste from Agaricus subrufescens and Pleurotus ostreatus showed promising results for arugula (Eruca vesicaria L.) and lettuce cultivation [12]. Substrates of vermicompost, compost, and anaerobic digestion in sage cultivation show no significant difference in terms of chemical composition, yield, and essential oil composition when compared to peat cultivation [13]. The oyster mushroom was grown in four different substrates: baobab (Adansonia digitata L.) fruit shell, wheat (Triticum aestivum L.) straw, sawdust, and maize (Zea mays L.) cobs, with the following yields: sawdust (682 g) > wheat straw (594 g) > maize cobs (518 g) > baobab fruit shell (482 g) [14].…”
Section: Soilless Substrate Culturementioning
confidence: 99%